Effect of probiotic and sand filtration treatments on water quality and growth of tilapia (Oreochromis niloticus) and pangas (Pangasianodon hypophthalmus) in earthen ponds of southern Bangladesh. Issue 3 (2nd July 2016) - Mahmud, Sultan; Ali, Mohammad Lokman; Alam, Md. Ariful; Rahman, Md. Mizanur; Jørgensen, Niels O. G.
ABSTRACT: Effects of water treatment by two probiotic products (PondPlus® and AquaPhoto®) and sand filtration were studied on growth performance of tilapia ( Oreochromis niloticus ) and pangas ( Pangasianodon hypophthalmus ) stocked at tilapia:pangas ratio of 5:3 in traditional earthen ponds in Bangladesh. The fish were stocked at a density of 20, 000 fish ha −1 and reared for 7 months. Compared to untreated ponds, treatments of probiotic products or sand filtration in earthen ponds resulted in a higher O2 content, higher water transparency, less ammonium, and fewer cyanobacteria. Weight gain for individual tilapia was lowest in the AquaPhoto-treated ponds (177 g), while similar gains (188–194 g) occurred in the other ponds. For pangas, the lowest weight gain (627 g) was obtained in the sand filter-treated ponds, as compared to 690–797 g in the other ponds. Thus, a general positive effect from the treatments on fish growth was not observed, possibly due to a reduced content of detritus (supplementary feed for both fish species) in the treated ponds.